2020
DOI: 10.4314/agrosh.v19i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Economic implication of contract farming on small-scale rice farmers in Kwara State, Nigeria

Abstract: This study examines the implication of contract farming on Olam Out-growers farming scheme in Kwara State, Nigeria. The objectives of the study are to determine the costs and returns to production of rice, assess the productivity level of rice, evaluate the technical efficiency of rice farm and identify the determinants of the technical inefficiency of the rice farms in contract farming. In this study, the average net farm income of the rice farmers under the scheme was N191,862.56 and the land productivity le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…This implies that contract farmers were still in their active and productive where innovative ideas and improved farming practices capable of improving their livelihood status are adopted. The finding concurs with that of Akanbi et al (2019 2 revealed that 86.9% of the contract farmers in were married indicating family responsibilities that will influence rice farmers" participation in contract farming in order to enhance rice farmers livelihood status. This finding is in consonance with that of Namso and Gabriel (2015) who opined that majority of contract fishermen in Akwa-Ibom State, Nigeria were married.…”
Section: Results and Discussion Socioeconomic Characteristics Of Cont...supporting
confidence: 87%
“…This implies that contract farmers were still in their active and productive where innovative ideas and improved farming practices capable of improving their livelihood status are adopted. The finding concurs with that of Akanbi et al (2019 2 revealed that 86.9% of the contract farmers in were married indicating family responsibilities that will influence rice farmers" participation in contract farming in order to enhance rice farmers livelihood status. This finding is in consonance with that of Namso and Gabriel (2015) who opined that majority of contract fishermen in Akwa-Ibom State, Nigeria were married.…”
Section: Results and Discussion Socioeconomic Characteristics Of Cont...supporting
confidence: 87%
“…The majority of the rice farmers using certified seeds had an educational background, while about 44% of the users of farmers' seeds had no formal education. Thus, educated farmers embrace the adoption of new technology more than uneducated ones (Akanbi et al. , 2020; Mukaila et al.…”
Section: Resultsmentioning
confidence: 99%
“…1 March 2024Page: 281 -296| 283 2020. Contract farming in Africa is mainly promoted by private sector like private companies/individuals with little support from public institution, that is Public-Private Partnerships (PPPs) (Oladapo et al, 2023;Akanbi et al, 2019;Adebisi et al, 2020). According to and Barrowclough et al (2019), many contract farming schemes in less developed countries are multipartite arrangements involving private firms (usually foreign, but occasionally local with examples such as OLAM, BATIAL and Nestle SLAMARK in Nigeria), the host-country government, and international aid or lending agencies, such as the U.S. Agency for International Development (USAID), the World Bank, or the Commonwealth Development Corporation (CDC).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that with such an arrangement, farmers agree to deliver certain quantities of a specific product at the quantified eminence criteria and time, and the buyer might also supply some inputs or hands-on backing to the farmer such as better technology, coordinating producers and consumer's market along with strong grass-root linkages (Adebisi et al, 2020& Akanbi et al, 2019. The contract farming models usually provide farmers with services like access to credit; extension service, agricultural production inputs; training on good agronomic practices, farm supervision, storage facilities, and readily available markets for harvested crops among other services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation